SOCIO DEMOGRAPHIC FACTORS OF PARENTAL STRESS DURING COVID-19 PANDEMIC RELATED LOCKDOWN IN PAKISTAN - Bilal, Ahmad; Khalid, Zahida; Fatima, Sana (Pakistan Journal of Physiology, 2021)
Background: There had been recent Western studies that reported the parental stress during COVID-19 pandemic. The present study was designed with an aim to find out the socio-demographic factors of parental stress in a sample of parents in Punjab province of Pakistan. Methods: Four hundred and sixty-six (466) parents were recruited from different cities of Punjab by administering a Google form based cross-sectional survey over social media platforms including WhatsApp and Facebook. The study was conducted from March to May 2020. The Urdu standardized version of Parental Stress Scale was administered as the main measure. Each participating parent was requested to give explicit consent before enrolling for the study. The data was analysed using SPSS-25. Results: There were statistically significant differences in parental stress with respect to marital status, age, gender, and employment status of parents. On the other hand, there were no statistically significant differences in parental stress with respect to the number and age of children, and education of the parents. Conclusion: There were 7 socio-demographic factors of parental stress. Some of those factors impact parental stress while some other factors did not impact parental stress. Future studies may be conducted with participants from other provinces too and by including other parenting related variables.